Pelatihan Digital Marketing WhatsApp Group bagi Kelompok Usaha Rumah Tangga Desa Klambir Lima Kebun Kabupaten Deli Serdang Provinsi Sumatera Utara - Dewi Mahrani Rangkuty; Hidayati Purnama Lubis; Herdianto Herdianto; Mita Mutiara Zora (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2022)
This service activity aims to improve the knowledge and skills of the Klambir Lima Kebun Village household business group through the establishment of WhatsApp Group digital marketing as one of the efforts in improving business product marketing strategies. This devotion activity uses training methods with the target of village household business groups as objects of service that amount to Â± 40 people. The results of this service activity show that the limitations of digital literacy are one reason that triggers the target of marketing business group actors' products has not been in line with expectations, so this devotion activity has also succeeded in creating a WhatsApp Group with four business groups. Village officials can continue to support those who help in every training/education activity carried out by institutions, institutions, or other private parties to maintain the sustainability of household businesses in rural environments.